Pengaruh Pendapatan, Religiusitas, dan Literasi Keuangan terhadap Keputusan Menabung di Bank Syariah, Bungo, Jambi. - Furnawati, Raudhah; Ferawati, Rofiqoh; Mubyarto, Novi (Jurnal Paradigma Ekonomika, 2022)
This study aims to determine partially and simultaneously whether or not the variables of income, religiosity and financial literacy influence the decision to save in Islamic banks. This research is a quantitative research. With primary and secondary data collected. The data collection technique obtained is by means of a questionnaire (questionnaire) and data on the development of Islamic banking on the official website of the Financial Services Authority (OJK). The people of Bungo Regency who already have savings in Islamic banks are the sample in this study, amounting to 100 people. The analysis used is multiple linear regression analysis with the help of SPSS. This study resulted in four things, namely: (1) there is a positive influence between income variables on the decision to save in Islamic banks (2) there is a positive influence between the religiosity variable on the decision to save in Islamic banks, (3) there is a positive influence between literacy variables financial decisions on saving decisions in Islamic banks and (4) indicate that income, religiosity, and financial literacy (simultaneously) have a positive effect on decisions to save in Islamic banks as much as 79.1%, the remaining 20.9% is influenced by other factors that not investigated in this study.